Tocilizumab and Abatacept for the Treatment of Childhood Chronic Uveitis: A Monocentric Comparison Experience - Maccora, Ilaria; Abu Rumeileh, Sarah; Curci, Franco; de Libero, Cinzia; Marrani, Edoardo; Mastrolia, Maria Vincenza; Pagnini, Ilaria; Simonini, Gabriele (Frontiers in Pediatrics, 2022)
Background The aim of our study was to evaluate the efficacy of Tocilizumab and Abatacept for treating uveitis Childhood Chronic non-infectious Uveitis (CCU), resistant to anti-TNF treatment. Methods. This is a monocentric retrospective charts review study (January 2010 - April 2021) recruiting CCU, refractory to anti-TNF. To be included, children should have active uveitis at the time of Tocilizumab (8 mg/kg, every 4 weeks) or Abatacept (10 mg/kg, every 4 weeks) starting. The main outcome was the achievement of ocular remission on treatment defined as the absence of flares for ≥ 6 months. Results. 18 CCU patients (14 F), previously treated with Methotrexate and Adalimumab, were enrolled: 15 had Juvenile Idiopathic arthritis (83.3%), 2 idiopathic (11.1%), and 1 Behçet (5.6%). Ten patients received Abatacept, 8 patients Tocilizumab. The mean duration of treatment on Abatacept was 31.6 months (SD ±30.8), on Tocilizumab 25.25 months (SD±17.8). Thirteen children (72.2%) achieved remission, with a better remission rate for Tocilizumab group (8/8) compared to Abatacept group (5/10) (χ² 5.53, p=0.019). No difference was evaluated between the two groups in the proportion of patients who showed flares during the treatment (2/6 Abatacept vs 1/8 Tocilizumab). A significant difference was evaluated in the proportion of patients who flared after treatment discontinuation: 3/3 Abatacept vs 0/3 Tocilizumab (χ² 3.8, p=0.025). Conclusions. Even though this is a monocentric retrospective study, in a relatively small group, our study suggests a superior efficacy of Tocilizumab over Abatacept for treating anti-TNF refractory CCU.